2009
DOI: 10.1016/j.proche.2009.07.317
|View full text |Cite
|
Sign up to set email alerts
|

Smart optical CMOS sensor for endoluminal applications

Abstract: A custom CMOS image sensor for capsular endoscopy is presented. The complete functionality of the chip is guaranteed through seven signal pins, used for the I 2 C like input and the LVDS output interfaces. Prototypes have been produced in the UMC 0.18µm-CIS (CMOS Image Sensor) technology both in the monochrome and colour-RGB versions. The imager has been electrically and optically characterized and ex-vivo images have been acquired and evaluated. The results of the characterization show state of the art perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…When compared with the PillCam SB, it has been shown that the EndoCapsule generally scores higher in image quality and resolution, but both yield comparable diagnostic performance [46,47]. CMOS technology has also been applied to a variety of robotic capsules within the Versatile Endoscopic Capsule for Gastrointestinal Tumor Recognition and Therapy (VECTOR) European project, where a monolithic 320 × 240 active-pixel colour-RGB or grey level camera-on-a-chip sensor was developed and tested in the ex-vivo setting [48,49].…”
Section: Image Acquisition Hardwarementioning
confidence: 99%
“…When compared with the PillCam SB, it has been shown that the EndoCapsule generally scores higher in image quality and resolution, but both yield comparable diagnostic performance [46,47]. CMOS technology has also been applied to a variety of robotic capsules within the Versatile Endoscopic Capsule for Gastrointestinal Tumor Recognition and Therapy (VECTOR) European project, where a monolithic 320 × 240 active-pixel colour-RGB or grey level camera-on-a-chip sensor was developed and tested in the ex-vivo setting [48,49].…”
Section: Image Acquisition Hardwarementioning
confidence: 99%
“…In the meantime, a large set of capsule-dedicated modules has been produced by the scientific community, enabling quality improvement. These devices range from electromechanical actuators for biopsy [9,10], locomotion [11][12][13] and therapy [14], to purely electronic systems to improve transmission rate and image resolution [15,16]. Unfortunately, due to their high power consumption and the lack of available power, these modules cannot be embedded in the currently available capsules.…”
Section: Introductionmentioning
confidence: 99%